Mental Health Programs for the UK-Based LGBTQ Community Through Education and Employment Opportunities - Tharakan, Jacob Ninan (Asian Journal of Public Health and Nursing, 2024)
Background: This study explores mental health programs designed for the LGBTQ community, focusing on education and employment opportunities as a way to improve mental wellbeing. Methods: This Systemic Review evaluate existing mental health programs for LGBTQ individuals in the UK. It consider factors such as economic disparities, social inequalities, and communication barriers faced by LGBTQ individuals. They will draw on demographic data and scholarly research to highlight the importance of inclusive education policies and job opportunities. Results: The evaluation plan outlined in this study emphasizes a research design incorporating observational methods and measurement of various factors, such as social behaviour, job satisfaction, and skill enhancement. The researchers will also involve relevant stakeholders, including government agencies and NGOs, for the successful implementation of these mental health programs. Conclusions: By prioritizing the needs of the LGBTQ community and collaboration among stakeholders, this study aims to contribute to the advancement of mental health initiatives that promote inclusivity and equity by maintaining equal opportunities.